Mesoscopic Characteristics and Performance Evaluation of Loess Treated by Different Anti-Seismic Subsidence Technologies - Wang, Ping; Xu, Shuya; Shao, Shengjun; Wang, Huijuan; Li, Xudong; Qian, Ziling (Frontiers in Earth Science, 2022)
The meso-structure of the soil has an important restriction on its engineering properties. Based on dynamic triaxial tests and SEM meso-structure test experiments, this study investigated the meso-scale structural deformation characteristics of Q3 loess samples treated by physical, chemical, and compound improvement methods, before and after strong earthquakes of typical seismic subsidence loess. On this basis, the seismic subsidence performance of the improved method is given under the conditions of frequent earthquakes, fortifying earthquakes, and rare earthquakes. The results show that 1) the physical improvement method has the most obvious effect on the elimination of macropores and overhead pore structures; 2) the chemical method can generate unique glass beads or flocculated fine structures, which can greatly enhance the strength of the soil and play the role of filling, cementing, or buffering, respectively, in the event of a strong earthquake; 3) for several improved treatment methods, the amount of seismic subsidence increases non-linearly with the increase in peak acceleration; and 4) in the event of frequent earthquakes, the earthquake subsidence can be eliminated by the method of adding fly ash, and when the fortification earthquake comes, the dynamic composite method can completely eliminate the seismic subsidence of the site. The related results can give reasonable suggestions for the treatment of seismic subsidence of different foundations in the “resilient urban and rural” and key engineering construction and seismic design of China’s loess area.